INVESTIGATION OF THE EFFECT OF MESH SIZE AND FRACTION VOLUME ON BENDING STRENGTH CHARACTERISTICS OF GEOPOLYMER COMPOSITE - Ridwan Afandi; Muhammad Munadi; Fajar Paundra; Sri Hastuti; Akhmad Nurdin (Program Studi Teknik Mesin, Universitas Muhammadiyah Surakarta, 2023)
Composite material is a material consisting of two or more type materials that have different properties, by combining macroscopically, and good interfacial bonds from one material to another. Currently, polymer composite materials are widely applied in the land, sea, and air transportation industries, moreover polymer composites with fire resistance properties have been developed with the addition of geopolymer that has the advantage of producing high performance. This study aims to determine the effect of mesh size and volume fraction of lightweight brick powder on flexural strength. The benefits of this research directly increase the economic value of lightweight brick waste and produce a tough advanced material at a low cost. The composite filling material used lightweight brick waste and sieved using a sieve with a level of 50, 100, 150, and 200 at a volume fraction of 45%, and a volume fraction of 0%, 15%, 30%, 45%, and 60% at a mesh 200. While the composite matrix used the thermoset polymer Ripoxy R-804. Based the result, addition of lightweight brick powder with variations in particle size of the lightweight brick powder and volume fraction showed a decrease in flexural strength resistance compared to those without lightweight brick powder.